Establishment of a risk assessment tool for pregnancy-associated venous thromboembolism and its clinical application: protocol for a prospective observational study in Beijing - Yi Chen; Yan Dai; Jing Song; Ling Wei; Ying Ma; Ning Tian; Qian Wang; Qian Zhang; Yue Zhang; Xiao Lan Wang; Jun Zhang; Rong Liu (BMC Pregnancy and Childbirth, 2019)
Abstract Background The risk of venous thromboembolism (VTE) during pregnancy and puerperal periods is significantly higher than during the non-pregnant period and is one of the major causes of maternal mortality. Developed countries have promulgated guidelines for risk assessment and prevention of maternal VTE, and standardized management has led to a significant reduction in maternal mortality. However, there is a paucity of relevant research related to pregnancy and puerperal VTE in China. Methods/design We will perform a prospective cohort study and recruit 13,000 pregnant women from 2018 to 2020 in Beijing, China. VTE risk assessment will be conducted using the Royal College of Obstetricians and Gynaecologists (RCOG) pregnancy and puerperal VTE risk-assessment-scoring tool during early and late pregnancy, as well as during the puerperal period. Venous ultrasonography of lower extremities, routine blood tests, and coagulation parameters will be examined. These VTE risk assessments will be performed again if patients have VTE-related symptoms during their pregnancies, or if any of the following occur: (1) patients are hospitalized over 7 days due to any pregnancy complications; (2) patients are placed under strict bed rest for ≥ 3 days to prevent miscarriage. For patients with a confirmed diagnosis of VTE, treatment and follow-up plans will be decided jointly by the obstetricians, vascular surgeons, and pulmonologists. All patients in the study will be followed up by dedicated healthcare providers for up to 42 days postpartum. Statistical analyses will be performed to test the feasibility of the RCOG scoring tool for the Chinese population. The RCOG scoring tool will then be revised based upon the characteristics of the Chinese population, and the revised assessment scoring tool will then be tested in the cohort to evaluate its efficacy. Finally, a pregnancy and puerperal VTE risk-assessment tool will be proposed based on our study results. Discussion This study will establish a preliminary VTE risk-assessment tool that is applicable to pregnant and puerperal women in China and provide guidelines for further thrombophylactic interventions. Furthermore, we wish to draw increased attention to pregnancy-associated VTE to reduce VTE-related mortality. Trial registration Chi CTR1800015848 (04/24/2018).